2012
DOI: 10.1002/brb3.31
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and suppression in a lexical interference fMRI‐paradigm

Abstract: Previous picture-word interference (PWI) fMRI-paradigms revealed ambiguous mechanisms underlying facilitation and inhibition in healthy subjects. Lexical distractors revealed increased (enhancement) or decreased (suppression) activation in language and monitoring/control areas. Performing a secondary examination and data analysis, we aimed to illuminate the relation between behavioral and neural interference effects comparing target-related distractors (REL) with unrelated distractors (UNREL). We hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 75 publications
(197 reference statements)
4
39
4
1
Order By: Relevance
“…Moreover, neither age group demonstrated priming‐related reductions in activation, which others have reported as decreases in activation in the superior temporal gyrus during the processing of phonological distractors relative to unrelated distractors (de Zubicaray & McMahon, ; de Zubicaray et al., ). Our results are more consistent with other recent studies (e.g., Abel et al., , ; Diaz, Hogstrom, et al., ), as younger adults showed increased activation in regions including the middle temporal gyrus, superior temporal gyrus, and supramarginal gyrus, many of these regions have been previously associated with phonological processing (e.g., Vigneau et al., ). Additionally, portions of these activations extend to the ventral portion of the precentral gyrus, which has previously been associated with articulatory processes (Brown, Ngan, & Liotti, ; Brown et al., ; Takai, Brown, & Liotti, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, neither age group demonstrated priming‐related reductions in activation, which others have reported as decreases in activation in the superior temporal gyrus during the processing of phonological distractors relative to unrelated distractors (de Zubicaray & McMahon, ; de Zubicaray et al., ). Our results are more consistent with other recent studies (e.g., Abel et al., , ; Diaz, Hogstrom, et al., ), as younger adults showed increased activation in regions including the middle temporal gyrus, superior temporal gyrus, and supramarginal gyrus, many of these regions have been previously associated with phonological processing (e.g., Vigneau et al., ). Additionally, portions of these activations extend to the ventral portion of the precentral gyrus, which has previously been associated with articulatory processes (Brown, Ngan, & Liotti, ; Brown et al., ; Takai, Brown, & Liotti, ).…”
Section: Discussionsupporting
confidence: 93%
“…However, other studies have reported an opposite pattern of activation, reporting that the presence of a phonological distractor results in increased activation. Increased activation has been observed in the left STG and SMG when compared to both semantic distractors (Diaz, Hogstrom, et al., ) and unrelated distractors (Abel et al., ), while activation of the bilateral middle temporal gyrus (MTG) has also been reported for phonological compared to unrelated distractors (Abel, Dressel, Weiller, & Huber, ). Overall, it appears as though target repetition may strongly influence whether phonological processing is associated with increased or decreased activation.…”
Section: Introductionmentioning
confidence: 99%
“…Ein erh ö hter Bedarf an Sprachkontrolle zeigte sich bei den Nebengeordneten in einer -verglichen mit der phonologischen Bedingung -st ä rkeren Aktivierung eines Areals, das f ü r die Ü berwachung von Konfl ikten verantwortlich ist (anteriorer Cortex cinguli (ACC) links): Eine unbeabsichtigte Produktion des st ö renden Konkurrenten musste verhindert werden. Bei den Unrelationierten war der Kontrollbedarf aber am st ä rksten, besonders deutlich wieder im Vergleich mit den Phonologischen [14] . Letztere ben ö tig ten nicht nur weniger Ressourcen in pr ä frontalen und cingul ä ren Arealen zur kognitiven Kontrolle, sondern auch in jenen Arealen, die f ü r neuronales Priming bei wiederholter visueller Objektvorgabe vorbeschrieben sind, darunter visuelle und konzeptuell-semantische Netzwerke.…”
Section: Bild / Wort-interferenzunclassified
“…We hypothesized three possible outcomes of our fMRI experiments: repetition enhancement [2527], repetition suppression [10, 2830], or both. Findings of mutual interference between the embedded words and their carriers in behavioral priming studies indicate a co-activation of the embedded words and their carriers [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…In either case, canceling out could occur, because although the latency of repetition suppression voxels is typically faster than the latency of repetition enhancement voxels (~3 s); due to poor temporal resolution of fMRI and the limitation of the current study, it would be impossible to detect such a difference [35]. Additionally, or alternatively, concurrent enhancement and suppression for the embedded words could co-occur in different brain regions based on sensitivity to visual versus language-related characteristics of stimuli (e.g., [27]).…”
Section: Introductionmentioning
confidence: 99%